The Acquisition Order of Past Tenses: An Interlanguage Analysis - Muhammad Ahkam Arifin; Suryani Jihad; Sri Mulyani; Hardiani Ardin; Nurwahida Nurwahida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
This study aimed to investigate the hypothesis that there appears a systematic order of the acquisition of past tenses. It is claimed that irregular past tense verbs are acquired earlier than regular past tense verbs. In comparison to the acquisition of irregular and regular past verbs, the acquisition of the past copula be forms `was` and `were` is believed to take place much earlier. To test this hypothesis, the data were collected from forty-six students who were asked to write an essay with a minimum of 250 words to get data of the use of past tenses. The findings reveal partial support for the hypothesis, suggesting that the universal order of morpheme acquisition may not be a stable phenomenon.